(untitled) (Fiep Bulletin - online, 2015)
We have seldom read any book with a similar interest. Not because of its great size, its thousand pages and excellent pictures. The principal motives are different and deserve to be expounded to the readers, i.e., to be numerous specialists who, for multiple reasons – technical, pedagogical, biological and even social ones – are interested in the problems of contemporary physical education.